Bioassessment dan Kualitas Air Daerah Aliran Sungai Legundi Probolinggo Jawa Timur - Meta Apriliawati Sandi; I Wayan Arthana; Alfi Hermawati Waskita Sari (Journal of Marine and Aquatic Sciences, 2017)
Legundi River is one of the six rivers in Probolinggo. Water is used for local community irrigation system of the rice fields. Makrozoobenthos was affected by the physical and chemical factors of the water condition. In order to determine the health of water in the river, it was applied water biological condition assessment technique by using biological parameter (bioassessment). This research used bioassessment with biotilik approach (invertebrate indicator of water quality) and Family Biotic Index (FBI). This research aimed to to find out the composition of biotilik, the water quality based on the physical and chemical factors, and the water status through biotilik indicator in Legundi River. This research was done in Legundi River on January until Pebruary 2017. The method which was used in this research was the direct observation by using purposive sampling to determine the location of the sampling. The result showed that the dominant biotilik composition was Hydropsychidae* (602), Thiaridae (258), and Parathelpusidae (209). The characteristics of the water from the upstream to downstream was as follows, temperature: 26,37 – 27,37 ?C, pH: 6,49 – 7,94, DO: 6,95 – 8,86 mg/l, turbidity: 1,16 – 3,58 NTU, BOD: 6,74 – 9,1 mg/l, and COD: 8,823 – 9,459 mg/l. The analysis of the biotilik index showed that the water was slightly clean with moderate pollution; and the analysis by using the Family Biotic Index showed that the water was not polluted.